PENGARUH KEMAMPUAN INTELEKTUAL DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA AGEN ASURANSI PADA PT PRUDENTIAL LIFE ASSURANCE CABANG PRUAINI PS8 PEMATANGSIANTAR - Siregar, Jhon Hendry; Lie, Darwin; Efendi, Efendi; Nainggolan, Nana Triapnita (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The results of this study can be summarized as follows: 1. The intellectual abilities, performance promotion and the performance of insurance agents is excellent. 2. The results of regression analysis is Å¶ = 10,850 + 0,494X1 + 0,418X2, means that intellectual abilities and performance promotion has a positive effect to job satisfaction insurance agents. 3. The results of the analysis correlations is r = 0,761, means that there is moderately high and positive between intellectual abilities, performance promotion and job satisfaction insurance agents. The results of determination is r square = 0,579, means that the level of job satisfaction insurance agents can be explained by intellectual abilities and performance promotion as big as 57,9%. As for the suggestion from the results of this research are: 1. To enchance the intellectual abilities more seriously insurance agent to understand the training, monday morning motivation (M3), business opportunity product (BOP) about insurance and understand the new insurance products. 2. To further enchance the performance promotion of the insurance agent should more seriously to following the seminar, training, offering insurance products with a variety of innovations, so that prospective clients interested ini having an insurance policy with such production targets are achived impact insurance agent job satisfaction optimization